From victim blaming to upstream action: tackling the social determinants of oral health inequalities - Watt RG. (Blackwell Synergy, 2007)
The persistent and universal nature of oral health inequalities presents a significant challenge to oral health policy makers. Inequalities in oral health mirror those in general health.